The Influence of Sufism in Buton: Expression in the Local Poetic Tradition of Kabhanti Bunga Malati - Hardin, Nurul Isra; Mubin, A. Faizul; Hakim, Lukmanul; Zakaria, M. Fadhlurrahman (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2025)
This article explains the concept of sufi ethics (tasawuf akhlaki) and its elaboration in the local poetry of Buton community, known as Kabhanti Bunga Malati. Khabanti is a Wolio language poem that is the result of the amalgamation of Buton Sultanate’s local culture with Islamic values, containing various Islamic teaching and wisdom. This research is a library research with the manuscript text of Kabhanti Bunga malati serves as the primary source of data, which is available in the online manuscript catalog of the British Library with the code EAP212/3/23. The Bunga Malati text is analyzed using Paul Ricoeur’s hermeneutical theory to uncover the meanings of symbols used in the text. The outcomes of this research indicate that the Khabanti Bunga Malati text elaborates the teachings of sufi ethics (tasawuf akhlaki) through the system of moral development known as takhalli, tahalli and tajalli. This reveals that the Khabanti Bunga Malati is seen and believed to be one of the initiatives of sufi education in the Buton Sultanate, which combines local cultural elements in the form of community poetry with Islamic values.